Transição das práticas de produção mais limpa para economia circular: survey por porte em indústrias têxteis localizadas no Brasil - Correia, José Manuel Ferreira (2020)
Industries play an important role for the global economy. However, its activities promote many debates regarding the negative impacts on the environment and on society itself. This research has as general objective to evaluate the transition from cleaner production practices (CP) to the circular economy (CE) by size of textile industries located in Brazil. The methodology adopted was a systematic literature review to identify the CE practices related to CP, followed by the application of a structured questionnaire through a survey to determine the degree of implementation of the CE practices by size of the textile industries. Then, in the process of results and discussion, the average value of CP practices was verified in relation to the average value of CE practices, which vary from 1 to 5, according to the Likert scale used in the survey, making it possible to assess how this situation is transition by company size. It should be noted that it was considered a published article that determined the degree of implementation of CP practices by size of the textile industry, being the starting point to verify the transition. Thus, with the collected data, the first analysis of the data quality was carried out through observation, then analyzed the relationship between variables and, finally, the necessary treatments in the data. Then, to compare the CE practices related to the size of the industries that made up the sample, the software of analysis of variances (ANOVA) was used. The results showed a greater degree of implementation of CE practices in large textile industries when compared to small and medium textile industries. The implementation of CE in an organization consists of the adoption of preventive actions. The implementation of CE in an organization consists of the adoption of preventive actions of at least one CE practice. CE is implemented when there is an increase in the reuse and recycling of textiles; for the reuse of waste generated; by the adoption of closed cycles in the production processes; elimination of waste; optimization of water and wastewater use; energy cogeneration and use of clean energy. These actions require the use of innovative technologies and investments. The transition from CP to CE practices provides theoretical, practical and social contributions, which are detailed in this study.